Effect of varying roof run-off coefficient values and tank size on rainwater harvesting system's water savings in Malaysia - Nasif, M.S. (Asian Research Publishing Network, 2016)
This study investigates the effect of using different roof run-off coefficient values in an office building in Malaysia on the water savings provided by rainwater harvesting system which is used to supply water for toilet flushing and irrigation purposes. In this paper rainwater harvesting system model is developed which reads the hourly rain fall data and calculates water consumption and savings. The harvesting tank sizes and roof run-off coefficient values were varied. It is found that as the values of roof run-off coefficient decreased, the amount of water saved remains almost unchanged for all investigated tanks sizes. A correlation is developed which relates roof run-off coefficient, volume of water saved and the tank sizes which can be used as useful design and sizing tool by buildings' designers to predict the amount of water saved for a specific rain water harvesting size. Â© 2006-2016 Asian Research Publishing Network (ARPN).